WelFur on-farm welfare assessment of foxes: development of behavioural tests - Mononen, Jaakko; Ojala, Eeva; Korhonen, Hannu T.; Koistinen, Tarja (Nordic Association of Agricultural Scientists, NJF, 2017)
Firstly, we studied associations between the two behavioural tests in the WelFur on-farm welfare assessment protocol for foxes. The Feeding Test (FT) is well validated and it measures human-animal relationship (HAR), whereas the more poorly validated Stick Test (ST) is assumed to measure one component of positive emotional state, namely explorative behaviour. Our results from the breeding animals of one commercial farm with both blue foxes (n = 690 females and 43 males) and silver foxes (n = 81 females and 24 males) show, however, that also the ST is probably rather a HAR test than a test of explorative behaviour. Accordingly, the less-laborious ST could probably substitute for the more laborious FT in the WelFur-Fox protocol. On the other hand, quite obviously a new test for assessing exploratory behaviour or positive emotional state in WelFur-Fox is needed. Secondly, we compared the results of the FT also to the results of a potential new test, a Subjective Evaluation of HAR (SE). In the SE the assessor recorded on a six-point scale a fox’s response to him/her (0 = approaches, 5 = withdraws) at the same time when recording other WelFur-Fox measurements from the animal and its cage. The SE is, thus, lesslaborious than the FT. The SE score distributions overlapped to some extent between the eaters (confident towards human) and non-eaters (not confident towards human) in the FT. This indicates either i) that the SE requires further development aiming at increasing its discriminative power before it could replace the FT in the WelFur-Fox protocol, or ii) that the SE has more fine-tuned discriminative power than the FT.